Don't sing before breakfast, don't sleep in the moonlight : everyday superstitions and how they began - Perl, Lila.; Weihs, Erika (New York : Clarion Books, 1988)
Examines common superstitions associated with the events of a typical day, how these superstitions developed, and how they influence our behavior today.
Includes bibliographical references and index.
Keywords: Superstition; Superstition